Phytostructural characterization of several vegetation types in northern Portugal. II. The structural expressivity and the resistance of the vegetation - Crespí, A.; Bernardos, S.; Castro, A.; Fernandes, C. P.; Amich, F. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract The encouraging results obtained in a previous work induced the authors to pursue here the characterization of the structure of the vegetation in northern Portugal, using the phytostructural methodology proposed earlier by the authors. With this objective, eight different types of vegetal communities, representative of the apparent states of the successional process present in this area, and representing the diversity of plant community types in the same area, were selected. The phytostructural method was elaborated on the basis of three types of structural basic matrices regarding diversity, abundance and cover. The data obtained were collected in a contingency matrix, which was then treated by means of a statistical multivariate analysis. Three structural tendencies emerged from this analysis. With the aim of studying their stability, the results are discussed in terms of resistance and resilience, according to the Highest Expressive Amplitude (HEA) concept, and by considering the intra- and inter-community structural dynamics as structural parameters. The data obtained suggest structural situations with different degrees of non-equilibrium that reflect resistance to environmental factors. The resistance of the vegetation is correlated with the apparent functional connectivity detected for the communities analysed.
doi: 10.1080/11263500500333651doi: 10.1080/11263500500333651The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Expressive capacity; multivariate analysis; Portugal; structural stability